أصول فقه الدعوة: دراسة تأصيلية تطبيقية - محمد بن فهد الحربي (مجلة العلوم الشرعية, 2024)
ملخص: موضوع البحث: (أصول فقه الدعوة: دراسة تأصيلية تطبيقية) ويندرج ضمن الإطار التأصيلي لعلم الدعوة، ويهدف إلى توضيح مفهوم أصول فقه الدعوة، وبيان صلة علم الدعوة بالأحكام التكليفية وقواعدها. وخلصتُ إلى نتائج، أهمها: إن علم أصول الدعوة هو العلم بالأسس والقواعد المتصلة بالدعوة وفهم أحكامها، وموضوع الدعوة وقضاياها هي نفسها مواضيع الدين: العقائد والأخلاق والتشريعات، والقرآن والسنة هما مرجع الدعوة في الاستدلال لأحكامها وقضاياها الكلية والجزئية. summary: Research topic: (Origins of Dawa jurisprudence: an applied, original study) and falls within the fundamental framework of Dawa science, and aims to clarify the concept of the principles of Dawa jurisprudence, and explain the relationship of Dawa science to obligatory rulings and their rules. I reached conclusions, the most important of which are: The science of the foundations of da’wah is knowledge of the foundations and rules related to da’wah and understanding its rulings. The subject of da’wah and its issues are the same as the topics of religion: beliefs, morals, and legislation. The Qur’an and Sunnah are the da’wah’s reference for inferring its general and partial rulings and issues.